2010
DOI: 10.1016/j.jacc.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Thrombus Healing to Underlying Plaque Morphology in Sudden Coronary Death

Abstract: Approximately two-thirds of coronary thrombi in sudden coronary deaths are organizing, particularly in young individuals-especially women, who perhaps might require a different strategy of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(149 citation statements)
references
References 20 publications
8
132
0
9
Order By: Relevance
“…Conversely, chronic thrombi showed the presence of spindle-shaped cells with or without macrophages that either lined the thrombus or infiltrated the thrombus, or had greater organization with matrix deposition interspersed between the fibrin. 12 Of a total of 21 thrombi, 13 had features of acute thrombi, whereas 8 had features that fulfilled the definition of chronic thrombi (organizing thrombus) Figure 6). In 9 patients, along with platelets, fibrin, and erythrocytes, some collagenous material was observed, but it was not possible to definitely identify whether this material was from the aortic valve or from the arterial wall ( Figure 4C and 4D).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Conversely, chronic thrombi showed the presence of spindle-shaped cells with or without macrophages that either lined the thrombus or infiltrated the thrombus, or had greater organization with matrix deposition interspersed between the fibrin. 12 Of a total of 21 thrombi, 13 had features of acute thrombi, whereas 8 had features that fulfilled the definition of chronic thrombi (organizing thrombus) Figure 6). In 9 patients, along with platelets, fibrin, and erythrocytes, some collagenous material was observed, but it was not possible to definitely identify whether this material was from the aortic valve or from the arterial wall ( Figure 4C and 4D).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Hearts of patients who had died suddenly with coronary artery disease (CAD) were obtained as previously described ( 13 ). Cases were identifi ed prospectively by the presence and type of CAD and included nonatherosclerotic intimal lesions, pathologic intimal thickening, early and late fi broatheroma, thin cap fi broatheroma (TCFA) and plaque rupture.…”
Section: Human Atherosclerotic Lesionsmentioning
confidence: 99%
“…Sato et al investigated the proportion of fibrin and platelets in thrombi of ruptured and eroded coronary atherosclerotic plaques obtained from patients who had died of acute MI within three days of onset and reported that fibrin was more abundant than platelets in the thrombi of ruptured plaques (74±19% vs. 35±20%, p<0.01), whereas platelets tended to be more abundant than fibrin in the thrombi of eroded plaques (51±6% vs. 70±21%, p<0.07) 16) . The second report was on the relationship between thrombus age (healing) and plaque morphology in sudden coronary death victims 82) . In that study, Kramer et al immunohistopathologically evaluated 111 sudden death victims who had coronary lesions (ruptures, n = 65; erosions, n = 50) with thrombi and determined the relationship between plaque morphology and thrombus healing classified as early (<1 day) or late characterized in phases of lytic (1 to 3 days), infiltrating (4 to 7 days) or healing (>7 days).…”
Section: Coronary Thrombus and Plaque Morphologymentioning
confidence: 99%